2021
DOI: 10.1371/journal.pone.0255325
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the association between exposure to family planning messages and consistent condom use among never married men in Ghana

Abstract: Background Despite considerable efforts to promote condom use, sexually active people in sub-Sahara Africa still engage in risky sexual behaviours, with condom use relatively low. With this high vulnerability of these persons to HIV and sexually transmitted infections, research related to exposure to family planning messages to help curb this trend remains sparse. This study examined how exposure to family planning messages in the midst of some socio-demographic factors is associated with consistent condom use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…The outcomes were in line with a study done in Ghana, where the majority of participants accurately stated that using condoms regularly, especially with those who have several partners, was one of the most efficient ways to engage in safe sex. 18 The findings support an Australian study that found the majority of participants believed having a single sexual partner was one of the safest ways to engage in sexual activity. 19 Regarding frequency of getting tested for STIs by a person engaged in unsafe sex, the results showed that most of the participants did not have an idea on the frequency of getting tested.…”
Section: Knowledge Factors On Safe Sex Practicesupporting
confidence: 78%
“…The outcomes were in line with a study done in Ghana, where the majority of participants accurately stated that using condoms regularly, especially with those who have several partners, was one of the most efficient ways to engage in safe sex. 18 The findings support an Australian study that found the majority of participants believed having a single sexual partner was one of the safest ways to engage in sexual activity. 19 Regarding frequency of getting tested for STIs by a person engaged in unsafe sex, the results showed that most of the participants did not have an idea on the frequency of getting tested.…”
Section: Knowledge Factors On Safe Sex Practicesupporting
confidence: 78%
“…One study which analysed the Ghana DHS found exposure to family planning messages is associated with a higher likelihood of consistent condom use among sexually active never-married men. 29 Using the level of education as a proxy for comprehensive knowledge of HIV, one study that analysed DHS data for 29 countries in SSA reports that among men who pay for sex, those that attained a secondary level of education are more likely to use condoms consistently. 30 In Uganda, less than half of the population aged 15–54 years have comprehensive knowledge of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…62 Hence, many health providers and promoters urged its use, especially among individuals at an increased risk of infection. [63][64][65] Several interventions have been employed in Ghana to encourage condom use. 48,49,63,66,67 One of the major intervention approaches in the country to increase condom use, especially among individuals who are at an increased risk of infection in Ghana is the Ghana Nation Condom and Water Based Lubricant Programming Strategy 2014-2019.…”
Section: Introductionmentioning
confidence: 99%
“…[63][64][65] Several interventions have been employed in Ghana to encourage condom use. 48,49,63,66,67 One of the major intervention approaches in the country to increase condom use, especially among individuals who are at an increased risk of infection in Ghana is the Ghana Nation Condom and Water Based Lubricant Programming Strategy 2014-2019. The intervention was a conscious approach by the government in collaboration with multiple nongovernmental and community-based organizations to identify barriers within Ghana that impacted condom use and employ strategies that addressed the needs of different segments of the Ghanaian population.…”
Section: Introductionmentioning
confidence: 99%